PENGARUH ADMINISTRASI PELAYANAN HAJI DAN UMRAH DI KANTOR KEMENTERIAN AGAMA TASIKMALAYA TERHADAP KENYAMANAN JAMAAH: Studi Kasus pada Kantor Kementerian Agama Tasikmalaya - Nurbaeti Affandie; Hasan Basri; Zaki Jaenal Arif (Prodi Manajemen Haji dan Umrah Fakultas Syariah UNIK Cipasung, 2024)
A private organization called Travel Hajj and Umrah was established with the aim of offering services for the departure of prospective pilgrims and Umrah pilgrims to the Holy Land. Hajj and Umrah travel agents must have a plan to attract more pilgrims and Umrah given the intense competition in the business sector. The purpose of this research is to understand the various forms of development tactics used by PT. Persada Taza Tours & Travel Umrah Tasikmalaya to attract the attention of pilgrims. Field studies of this kind use descriptive qualitative data analysis methods, including interviews and documentation. And all data is evaluated inductively. According to research, PT. Persada Taza Tours & Umrah Travel Tasikmalaya uses an expansion strategy as a new breakthrough in raising the interest of its congregation, especially through the partnership program and bokingsit savings system. However, there are obstacles in increasing the interest of pilgrims and umrah, including the lack of public understanding of the pilgrimage and umrah and the lack of interest of the residents of the city of Tasikmalaya in carrying it out. The purpose of this research is that Hajj and Umrah travel and business owners can improve the quality and capacity of prospective pilgrims and Umrah pilgrims to the Holy Land.